Shakespeare's Henry VIII: Stigmatizing the "Disabled" Womb - Nelson, Mary K. (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> In keeping with many disability theorists’ belief that disability is largely socially constructed, Shakespeare’s Henry VIII constructs Katherine of Aragon and Anne Boleyn as possessors of “disabled wombs.” Despite their proven fertility, for both women bear healthy daughters, their failure to birth sons leads to their depiction as disabled. The subsequent treatment that Katherine and Anne endure mirrors the experiences that disabled people have historically faced: they are blamed for their conditions, which are viewed as indicators of sinful activity, stigmatized, and sequestered, both from their own daughters and the world. The play concludes with the christening of Elizabeth, who resisted the pressure to conform to the biological paradigm of maternity and established herself as a metaphoric mother to her people. In so doing, Elizabeth escaped her own mother’s fate: designation as a disabled queen mother. Keywords: early modern maternity, early modern disability, Shakespeare’s Henry VIII